Aspectos de patogenicidade e relacionamento genético de isolados clínicos vaginas e anais de Candida albicans oriundos de pacientes com candidíase vulvovaginal - Medeiros, Mariana Araújo Paulo de (2013)
Vulvovaginal candidiasis (VVC) is one of the most common causes of vaginitis and affects about 75% of women of reproductive age. The majority of cases (80 to 90%) are due to C. albicans, the most virulent species of the genus Candida. Virulence attributes are scarcely investigated and the source of infection remains uncertain. Objective: This study aimed to evaluate the virulence factors and genotypes of clinical isolates of C. albicans sequentially obtained from the anus and vagina of patients with sporadic and recurrent VVC. Materials and methods: We analyzed 62 clinical isolates of C. albicans (36 vaginal and 26 anal strains). Direct examination of vaginal and anal samples and colony forming units (CFU) counts were performed. Yeasts were identified using the chromogenic media CHROMagar Candida® and by classical methodology, and phenotypically characterized regarding to virulence factors, including the ability to adhere to epithelial cells, proteinase activity, morphogenesis and biofilm formation. The genotypes of the strains were investigated with ABC genotyping, microsatellite genotyping with primer M13 and RAPD. Results: We found 100% agreement between direct examination and culture of vaginal samples. Filamentous forms were present in most of the samples of vaginal secretion, which presented CFU counts significantly higher than the samples of anal secretion. There was no statistically significant difference between virulence factors of infecting vaginal isolates and those presented by colonizing anal isolates; as well as for the comparison of the vaginal isolates from patients with different clinical conditions (sporadic or recurrent VVC). There was a decrease in the ability to adhere to HBEC, morphogenesis and biofilm formation of the vaginal isolates during the progress of infection. There was an association between the ability to express different virulence factors and the clinical manifestations presented by the patients. Genotype A was the most prevalent (93.6%), followed by genotype C (6.4%). We found maintenance of the same ABC genotype and greater prevalence of microevolution for the vaginal strains of C. albicans sequentially obtained. Vaginal and anal isolates of C. albicans obtained simultaneously from the same patient presented the same ABC genotype and high genetic relatedness. Conclusion: It is noteworthy that the proliferation of yeast and bud-to-hypha transition are important for the establishment of CVV. The expression of virulence factors is important for the pathogenesis of VVC, although it does not seem to be determinant in the transition from colonization to infection or to the installation of recurrent condition. Genotype A seems to be dominant over the others in both vaginal and anal isolates of patients with VVC. The most common scenario was microevolution of the strains of C. albicans in the vaginal environment. It is suggested that the anal reservoir constituted a possible source of vaginal infection, in most cases assessed